Deaf Mental Health Care. - Glickman, Neil S. (Counseling and psychotherapy., 2013)
This volume presents a state of the art account of the clinical specialty of mental health care of deaf people. Drawing upon some of the leading clinicians, teachers, administrators, and researchers in this field from the United States and Great Britain, it addresses critical issues from this specialty.